Perlindungan Hukum bagi Pihak Ketiga dalam Penggunaan Hak Tanggungan sebagai Jaminan - Devi Rosiana (JURNAL ILMIAH NUSANTARA, 2025)
Mortgage rights are a form of security interest that provides legal certainty and preferential rights to creditors in the event that the debtor fails to fulfill their obligations. However, in practice, mortgage rights not only affect the parties involved in the agreement but may also impact third parties with interests in the secured object, such as buyers, tenants, or other creditors. Therefore, effective legal protection is necessary to safeguard third parties from potential losses resulting from the execution of mortgage rights. This study aims to analyze the forms of legal protection granted to third parties within Indonesia's mortgage rights system. The discussion covers the principle of publicity in mortgage rights registration, the application of the precautionary principle in transactions, and the role of notaries inensuring transparency and validity of agreements. Additionally, this study examines various court decisions related to disputes between mortgage rights holders and third parties to understand the legal protection patterns applied in practice. The findingsindicate that legal protection for third parties in the use of mortgage rights as collateral can be enhanced through increased transparency in mortgage rights registration, stricter enforcement of due diligence obligations for involved parties, and the optimization of the notary's role in ensuring legal certainty. With improved protection mechanisms, third-party rights and interests can be better safeguarded, reducing the risk of disputes.